Hybridity on the Ground in Peacebuilding and Development Critical Conversations - Wallis, Joanne; Kent, Lia; Forsyth, Miranda; Dinnen, Sinclair; Bose, Srinjoy (ANU Press, 2018)
"Hybridity on the Ground in Peacebuilding and Development engages with the possibilities and pitfalls of the increasingly popular notion of hybridity. The hybridity concept has been embraced by scholars and practitioners in response to the social and institutional complexities of peacebuilding and development practice. In particular, the concept appears well-suited to making sense of the mutually constitutive outcomes of processes of interaction between diverse norms, institutions, actors and discourses in the context of contemporary peacebuilding and development engagements. At the same time, it has been criticised from a variety of perspectives for overlooking critical questions of history, power and scale. The authors in this interdisciplinary collection draw on their in‑depth knowledge of peacebuilding and development contexts in different parts of Asia, the Pacific and Africa to examine the messy and dynamic realities of hybridity 'on the ground'. By critically exploring the power dynamics, and the diverse actors, ideas, practices and sites that shape hybrid peacebuilding and development across time and space, this book offers fresh insights to hybridity debates that will be of interest to both scholars and practitioners. 'Hybridity has become an influential idea in peacebuilding and this volume will undoubtedly become the most influential collection on the idea. Nuance and sophistication characterises this engagement with hybridity.' - Professor John Braithwaite"